Big data : using smart big data analytics and metrics to make better decisions and improve performance - Marr, Bernard (Hoboken : John Wiley & Sons, 2015)
Convert the promise of big data into real world results There is so much buzz around big data. We all need to know what it is and how it works - that much is obvious. But is a basic understanding of the theory enough to hold your own in strategy meetings? Probably.
1. Smarter Business -- 2. S = STARTWITH STRATEGY -- 3. M = MEASURE METRICS AND DATA -- 4. A = APPLY ANALYTICS -- 5. R = REPORT RESULTS -- 6. T = TRANSFORM BUSINESS.
Includes index.
Keywords: DATA MINING